Persepsi Ibu Hamil pada Pelayanan Antenatal Care di Desa Bolorejo Kecamatan Kauman Kabupaten Tulungagung - Sulistina, Dewi Ratna (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2018)
The high maternal mortality rate or MMR in Indonesia is an important issue that needs to be handled seriously. AKI is a measure of maternal health success and is a barometer of health services in a country, if the rate is still high, it means that health services in the country are categorized not good (Adriansz, 2007). So one of the efforts that need to get attention in reducing AKI is through improvement of health service quality of pregnant and maternity mother especially through antenatal care. The purpose of this study to determine the perception of pregnant women on antenatal care (ANC) in the Bolorejo village, Kauman District, Tulungagung Regency. This research is a qualitative research with cross sectional research design. Variable in this research is pregnant woman's perception on antenatal care service with population counted 11 responden, using technique of non probability sampling saturated (census), where research tool used is structured interview guidance, research location in Bolorejo village, Kauman district, Tulungagung regency. Time of study in July 2017. Presentation of data in the form of pie chart. From the results of the study obtained the results of pregnant women's perception on antenatal care service in the village of Bolorejo District Kauman Tulungagung district based on the care of ANC 10T that has been given to pregnant women has not been fully achieved. This is indicated from the data of the majority of pregnant women have received antenatal care 8T (80%) While a small proportion of pregnant women have not received antenatal care 2T (20%) which includes TT immunization and laboratory examination related to pregnancy (PP test, Hb, Protein urine, Urine reduction). Pregnant women who do not get TT immunization that there is 1 pregnant women due to pregnant women check into the village midwife in late third trimester of pregnancy and approaching delivery. As for pregnant women who do not get laboratory tests related to pregnancy (PP test, Hb, urine protein, urine reduction) that is as many as 3 pregnant women because the pregnant women did not want to be examined for fear of injections and no signs of danger pregnancy accompanying pregnant women during pregnancy (seen from the characteristics of respondents based on maternal reproductive age in low risk categories, based on parity also low risk). For pregnant women who are afraid of injections have actually been motivated by health cadres and village midwives but pregnant women are still not pleased to do laboratory examination (Based on the perception of pregnant women to public services and services ANC indicates that the services provided by health personnel are in conformity with standards) So that an unacceptable ANC examination of the standard (10T) was caused by a low awareness of pregnant women themselves.Â Keywords: Perception, Pregnant Women, Antenatal Care